INISIASI MENYUSUI DINI TERHADAP SUHU BAYI BARU LAHIR DI PUSKESMAS DLANGGU MOJOKERTO - Yuni Susanti, Ika (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Newborns often suffer a decrease in body temperature, this is due to the inability of the newborn maintain body temperature, subcutaneous fat is not perfect, body surface area compared to body mass, and temperature of the cold environment. To keep babys body temperature to remain normal then it needs to be an effort. Handling baby hypothermia in BPS is to provide the heated lamp to increase the babys body temperature by providing a 100-watt lights. This research aims to determine the effect of Early Initiation of Breastfeeding on the newborns body temperature.This type of research is experimental research design with quassy experiment. The independent variable is the newborns body temperature without Early Initiation of Breastfeeding. Dependent variable is the body temperature of newborns with Early Initiation of Breastfeeding. Entire maternal population by 20 people. Samples from this research is maternal as many as 16 respondents. Sampling is using accidental sampling. Research conducted in Public Health Centre Dlanggu Mojokerto on May to June 2012. The collection of data using primary data. The instrument used a thermometer and checklist. The data presented in tables and frequency distribution were analyzed using Willcoxon test.Results of research found almost all (87.5%) newborns body temperature without experiencing hypothermia Initiation of Breastfeeding, the majority (75%) body temperature of newborns with normal Initiation of Breastfeeding, 0025 test results Willcoxon ρ <0.05, then the H1 acceptedThere are affect of Early Initiation of Breastfeeding on the newborns body temperature in Public Health Centre Dlanggu Mojokerto.Based on the results obtained early initiation of breastfeeding affect the newborns body temperature, for the handling of newborn infants who suffered hypothermia body temperature more effectively done Early Initiation of Breastfeeding.key words: Early Initiation of Breastfeeding, newborn body temperature